Examining the association between child development and parental mental health after preterm birth-related stress: a systematic review of the literature and meta-analysis protocol - Lotte Haverman; Cornelieke S H Aarnoudse-Moens; Joost G Daams; Gerbrich E van den Bosch; Kirsten S Muller; Celina E Henke (BMJ Open)
Introduction Preterm infants born before 32 weeks of gestation are generally admitted to a neonatal intensive care unit (NICU) to receive life-saving treatment, resulting in early exposure to stressful events. Yet, NICU admission is not only stressful for the infant but can also have a long-lasting negative impact on parental mental health, who may worry about their child. Parental mental health problems might affect child development through parental behaviour and the parent–infant relationship. Simultaneously, adverse child development after preterm birth can (further) elevate parental stress and mental health problems, straining parental behaviour, the parent–infant relationship and child development. This systematic review and meta-analysis aims to examine the association between preterm-born children’s development (<32 weeks’ gestation) and parental mental health after preterm birth-related stress following NICU admission at any point in time.Methods and analysis A systematic review will be performed and reported following the Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines. A concept-based search on preterm birth, child development and parental mental health is performed using MEDLINE, Embase, PsycINFO and Cochrane Library on 22 March 2024. Eligible are studies with original results on the association between child development after preterm birth (<32 weeks’ gestation) and parental mental health. Independent reviewers will screen the articles, assess study quality using a Newcastle-Ottawa or Cochrane tool and determine the quality of evidence using Grading of Recommendations, Assessment, Development and Evaluation. Meta-analyses are planned on the association between child development and parental mental health after preterm birth.Ethics and dissemination No ethical approval is required. The results will enhance knowledge of the association between child development and parental mental health after preterm birth-related stress following NICU admission. This might lead to adjustments in follow-up care, optimising outcomes for infants and parents. Findings will be published in an international, peer-reviewed ad open-access journal.PROSPERO registration number CRD42024518307.